Penggunaan Abreviasi dan Akronim dalam Berkomunikasi oleh Pengguna Media Sosial - Susi Ekalestari; Efendi Barus; Abdurrozzaq Hasibuan; Tristi Ananda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the use of abbreviations and acronyms in communication by social media users. Therefore, the problem in this research is focused on the formation of abbreviations and acronyms in communication on social media. Data collection was carried out by visiting 20 accounts on social media such as Instagram, Facebook, Twitter, and Whatsapp Groups and collecting forms of abbreviations and acronyms used by social media users. The data from this study are forms of abbreviations and acronyms that have been collected from social media. Furthermore, the data were analyzed qualitatively referring to the theory of Kridalaksana (2010). This study found that there are six forms of abbreviations and acronyms used by social media users, namely: 1. Perpetuation of the first letter of each component, 2. Perpetuation of the first two letters of each component, 3. Perpetuation of the first three letters of each component, 4. Perpetuation of the first two letters of the first component and the first three letters of the second component, 5. The preservation of the last syllable of each component, 6. The preservation of various letters and syllables that are difficult to formulate. Furthermore, there were also two formations of abbreviations and acronyms that did not fix to the rules for the formation of abbreviations and acronyms in the General Indonesian Spelling Guidelines, namely, first, the formation of abbreviations and acronyms by preserving the letters of two or three components based on sound or pronunciation of these components. Second, the formation of abbreviations and acronyms perpetuates elements or sounds that are considered to represent the meaning of the components experiencing abbreviations and acronyms. Both of these formations are carried out by perpetuating any letters and syllables of one component that appear to have no relationship or connection with the components undergoing the process of abbreviations and acronyms.